2022
DOI: 10.1021/acs.jcim.2c00847
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Retention Time and Collision Cross Section (CCSH+, CCSH–, and CCSNa+) of Emerging Contaminants Using Multiple Adaptive Regression Splines

Abstract: Ultra-high performance liquid chromatography coupled to ion mobility separation and high-resolution mass spectrometry instruments have proven very valuable for screening of emerging contaminants in the aquatic environment. However, when applying suspect or nontarget approaches (i.e., when no reference standards are available), there is no information on retention time (RT) and collision cross-section (CCS) values to facilitate identification. In silico prediction tools of RT and CCS can therefore be of great u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 49 publications
0
21
0
Order By: Relevance
“…Most prediction models or workflows previously reported discuss one or the other predicted property (CCS or Rt), while only a few associate multi-dimensional information for metabolite annotation [ 47 , 48 , 49 , 50 ]. Interestingly, all of them are dedicated to lipids or exogenous compounds, while our workflow predicted a database including small molecules found in the human body, including water-soluble or lipid-soluble endogenous metabolites and exogenous compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Most prediction models or workflows previously reported discuss one or the other predicted property (CCS or Rt), while only a few associate multi-dimensional information for metabolite annotation [ 47 , 48 , 49 , 50 ]. Interestingly, all of them are dedicated to lipids or exogenous compounds, while our workflow predicted a database including small molecules found in the human body, including water-soluble or lipid-soluble endogenous metabolites and exogenous compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a few studies had been reported on a prediction model with multiple prediction functions, allowing prediction in multiple dimensions 148,157 . One of which was conducted by Celma et al 157 in which prediction of RT and CCS was performed simultaneously for suspect screening (SS) and nontarget screening (NTS).…”
Section: Ccs Modelsmentioning
confidence: 99%
“…This study was based on two algorithms (support vector machine Interestingly, a few studies had been reported on a prediction model with multiple prediction functions, allowing prediction in multiple dimensions. 148,157 One of which was conducted by Celma et al 157 in which prediction of RT and CCS was performed simultaneously for suspect screening (SS) and nontarget screening (NTS). Three individual models were built for RT, CCS for (de)protonated molecules (CCS H ), and CCS for sodiated molecules (CCS Na ), all based on the multivariate adaptive regression splines (MARS) model.…”
Section: Regression Modelsmentioning
confidence: 99%
“…For example, ML has been demonstrated to accurately predict t R across multiple environmental matrices, collision cross section in ion mobility spectrometry and to support identication and annotation of compounds during non-target HRMS. 28,[31][32][33] These predictive models would complement the CNN developed here to improve annotation of unknown compounds. Moreover, the advantage of HRMS enables retrospective analysis to improve current knowledge related to exposure and risk.…”
Section: Papermentioning
confidence: 99%